Formulation and evaluation of buccoadhesive tablets of clotrimazole - Reza, Tahvilian; Sara, Moosavi S (Asian Journal of Pharmaceutics (AJP), 2014)
The buccoadhesive tablet is one of delivery systems that can be used for different drugs in order to improve the efficacy of drugs in patients. Hydrophilic polymers are using to prepare these types of tablets with appropriate adhesion and stability in order to deliver the drug for a period of time and also in a specific place in month.The purpose of the study was to formulate and evaluate mucoadhesive buccal tablets of clotrimazole.The tablets were evaluated for weight variation, hardness, friability, disintegration, content uniformity, surface pH, mucoadhesive strength, swelling index and in vitro drug release. Increasing hydroxypropylmethylcellulose (HPMC) concentration resulted in decreasing the swelling index and increasing surface pH.The surface pH of all tablets was found to be satisfactory, close to neutral pH; hence, no irritation would observe with these tablets.The maximum bioadhesive strength was observed in tablets formulated with high content of HPMC. Lower release rates were observed by increasing the content of HPMC in the formulation The in vitro release results demonstrated that drug is released by non-Fickian diffusion mechanism with zero-order kinetics.